Beyond Allotypes: The Influence of Allelic Diversity in Antibody Constant Domains - Warrender, Annmaree K.; Kelton, William (Frontiers in Immunology, 2020)
Polymorphic diversity in antibody constant domains has long been defined by allotypic motifs that cross-react with the sera of other individuals. Improvements in sequencing technologies have led to the discovery of a large number of new allelic sequences that underlie this diversity. Many of the point mutations lie outside traditional allotypic motifs suggesting they do not elicit immunogenic responses. As antibodies play an important role in immune defense and biotechnology, understanding how this newly resolved diversity influences the function of antibodies is important. This review compiles the current known diversity of antibody alleles at a protein level for each antibody isotype as well as the kappa and lambda light chains. We focus on evidence emerging for how these mutations perturb antibody interactions with antigens and Fc receptors that are critical for function, as well as the influence this might have on the use of antibodies as therapeutics and reagents.